Pyroelectric power generation in PLZST material by temperature dependent phase transformation. Issue 6 (15th March 2022) - Sugiyama, Hironari; Kim, Juyoung; Yamanaka, Satoru; Kim, Yoonho; Ngo, Nguyen Chi Trung; Wiff, Juan Paulo; Suzuki, Tsuneo; Baba, Masaaki; Takeda, Masatoshi; Yamada, Noboru; Sekino, Tohru; Hashimoto, Hideki; et al.
Abstract: Efforts are being made to increase the efficiency of energy consumption by effectively using the dissipated heat as a source of renewable energy. Herein, we focused on a heat source wherein the temperature varies with time and recovers electrical energy from thermal energy by the pyroelectric effect. Further, we evaluated the net power density of the (Pb, La) (Zr, Sn, Ti)O3 material that is produced by its phase transformation as a result of increase in temperature. It was measured by the Sawyer-Tower circuit that was installed a diode and switch. The results showed that when the low or high temperature side of the measurement environment is in the antiferroelectric phase, the net power density decreased or became negative. Additionally, we estimated the range of temperature wherein a high-power density could be attained by examining the changes in it due to phase transformation.